Open carry - Cameron, Marc (Cameron, Marc. Arliss Cutter novel., 2019)
Skilled tracker U.S. Marshal Arliss Cutter must leave his comfort zone in the Florida swamplands to investigate the murder of a Tlingit Indian girl in the wilds of southeast Alaska.